Review of methodological choices in LCA of biorefinery systems ‐ key issues and recommendations. (24th April 2015) - Ahlgren, Serina; Björklund, Anna; Ekman, Anna; Karlsson, Hanna; Berlin, Johanna; Börjesson, Pål; Ekvall, Tomas; Finnveden, Göran; Janssen, Matty; Strid, Ingrid
Abstract: The current trend in biomass conversion technologies is toward more efficient utilization of biomass feedstock in multiproduct biorefineries. Many life‐cycle assessment (LCA) studies of biorefinery systems have been performed but differ in how they use the LCA methodology. Based on a review of existing LCA standards and guidelines, this paper provides recommendations on how to handle key methodological issues when performing LCA studies of biorefinery systems. Six key issues were identified: (i) goal definition, (ii) functional unit, (iii) allocation of biorefinery outputs, (iv) allocation of biomass feedstock, (v) land use, and (vi) biogenic carbon and timing of emissions. Many of the standards and guidelines reviewed here provide only general methodological recommendations. Some make more specific methodological recommendations, but these often differ between standards. In this paper we present some clarifications (e.g. examples of research questions and suitable functional units) and methodological recommendations (e.g. on allocation). © 2015 Society of Chemical Industry and John Wiley & Sons, Ltd